2022
DOI: 10.5194/acp-22-15263-2022
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric particle abundance and sea salt aerosol observations in the springtime Arctic: a focus on blowing snow and leads

Abstract: Abstract. Sea salt aerosols play an important role in the radiation budget and atmospheric composition over the Arctic, where the climate is rapidly changing. Previous observational studies have shown that Arctic sea ice leads are an important source of sea salt aerosols, and modeling efforts have also proposed blowing snow sublimation as a source. In this study, size-resolved atmospheric particle number concentrations and chemical composition were measured at the Arctic coastal tundra site of Utqiaġvik, Alask… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 132 publications
(304 reference statements)
2
5
0
Order By: Relevance
“…Sellegri et al and Fuentes et al found the 300 nm mode in air-forced bubble bursting chamber experiments with seawater samples from the Mediterranean Sea and around New Zealand. The 30 nm mode was also found in other studies in several regions ,, including the Arctic . We hypothesize that these observed modes are related to the composition of the particles, as discussed later.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Sellegri et al and Fuentes et al found the 300 nm mode in air-forced bubble bursting chamber experiments with seawater samples from the Mediterranean Sea and around New Zealand. The 30 nm mode was also found in other studies in several regions ,, including the Arctic . We hypothesize that these observed modes are related to the composition of the particles, as discussed later.…”
Section: Resultssupporting
confidence: 82%
“…The 30 nm mode was also found in other studies in several regions 68 , 70 , 71 including the Arctic. 72 We hypothesize that these observed modes are related to the composition of the particles, as discussed later.…”
Section: Resultsmentioning
confidence: 83%
“…Therefore, the conventional thinking is that while SSAs often contribute substantially to or even dominate high-latitude aerosol mass concentration 14 , 15 and direct radiative effect 26 , their influences on CCN concentration ( N CCN ) and cloud properties are less pronounced 25 , 26 . A recent modelling study in the Antarctic suggests blowing-snow sublimation may generate a substantial amount of fine-mode particles 27 , and elevated concentrations of fine-mode particles during blowing-snow events at a coastal Alaskan Arctic site are reported in a recent observational study 28 . Both studies raise the possibility that blowing-snow-produced SSA may strongly affect the Arctic climate by impacting the CCN population and the properties of clouds.…”
Section: Mainmentioning
confidence: 92%
“…Finally, blowing snow over the sea ice could serve as an additional source of atmospheric Na + aer when a certain air-temperature-dependent wind speed threshold is exceeded (Chen et al, 2022;Huang and Jaeglé, 2017;Yang et al, 2008). Consequently, connections and correlations for the release of SSA particles in the heterogeneous high Arctic are more difficult to explore than other marine environments without sea ice.…”
Section: Sea Spray Aerosol and Therein Contained Combined Carbohydratesmentioning
confidence: 99%